Fringe quality map for fringe projection profilometry in LabVIEW (2018)
The phase retrieval process is mainly affected by local shadows, irregular surface brightness and fringe discontinuities. To overcome these problems, image-processing strategies are carried out such as binary masks, interpolation techniques, and filtering. Similarly, many unwrapping algorithms have been developed to handle phase unwrapping errors in two-dimensional regions. The presence of error-prone areas can be visualized during the acquisition stage avoiding the use of image processing strategies and sophisticated phase unwrapping algorithms, which in many cases represent high computational costs and long execution times. To help overcome these problems, we propose a Fringe Quality Map based on a phase residue analysis to estimate error-prone areas during acquisition. The software was fully implemented in LabVIEW, and we provide the software as supplementary material. Experimental results demonstrate that the proposed method estimates areas with poor contrast, which lead to unwrapping errors, as well as phase errors in a more complex 3D shape. © Sociedad Española de Óptica.